Cultural feminism versus post-structuralism: The identity crisis in feminist theory - Alcoff, Linda (Signs, 1988)
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; cycles supérieurs; discipline; fem1000; fem9000; femmes*; identité sexuelle; philosophie; post-structuralisme; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; états-unis; études culturelles

The social origins of private life: A history of American families, 1600-1900 - Coontz, Stephanie (Verso, 1988)
Current debates about the future of the family are often based on serious misconceptions about its past. Arguing that there is no biologically mandated or universally functional family form, Stephanie Coontz traces the complexity and variety of family arrangements in American history, from Native American kin groups to the emergence of the dominant middle-class family ideal in the 1890s. Surveying and synthesizing a vast range of previous scholarship, as well as engaging more particular studies of family life from the seventeenth to the nineteenth centuries, Coontz offers a highly original account of the shifting structure and function of American families. Her account challenges standard interpretations of the early hegemony of middle-class privacy and “affective individualism,” pointing to the rich tradition of alternative family behaviors among various ethnic and socioeconomic groups in America, and arguing that even middle-class families went through several transformations in the course of the nineteenth centure. The present dominant family form, grounded in close interpersonal relations and premised on domestic consumption of mass-produced household goods has arisen, Coontz argues, from a long and complex series of changing political and economic conjunctures, as well as from the destruction or incorporation of several alternative family systems. A clear conception of American capitalism’s combined and uneven development is therefore essential if we are to understand the history of the family as a key social and economic unit. Lucid and detailed, The Social Origins of Private Life is likely to become the standard history of its subject.
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amériques; approches et analyses; cours; discipline; division of household labor; division sexuelle du travail; famille; féminisme matérialiste; his4443; histoire; histoire et politique; premier cycle; périodes historiques; rapports de classe; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; sociologie de la famille; thématiques; travail; travail domestique; états-unis

chapitre 3, « Les couvents comme expression organisée des aspirations des femmes » dans Profession: religieuse : un choix pour les Québécoises, 1840-1920 - Danylewycz, Marta; Linteau, Paul-André; Prentice, Alison; Westfall, William (Profession: religieuse : un choix pour les Québécoises, 1840-1920, 1988)
Marta Danylewycz s'intéresse à 2 communautés: les soeurs de Notre-Dame et de la Miséricorde, qui rassemblent près du cinquième de la population religieuse féminine au tournant du siècle.
Section: 246 pages : illustrations ; 22 cm
Keywords: 1800-1899; 1840-1849; 1850-1859; 1860-1869; 1870-1879; 1880-1889; 1890-1899; 1900-1909; 1900-1999; 1910-1919; amérique du nord; amériques; approches et analyses; canada; care; cours; discipline; discours dominant; his4550; histoire; histoire et politique; patriarcat; premier cycle; périodes historiques; québec; religion; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques

Pornography and civil rights: a new day for women's equality - Dworkin, Andrea; MacKinnon, Catharine A. (Organizing Against Pornography, 1988)
"Pornography is central in creating and maintaining the civil inequality of the sexes. Pornography is a systematic practice of exploitation and subordination based on sex which differentially harms women. . . ." With those bold words began the groundbreaking local antipornography law drafted by writer Andrea Dworkin and lawyer Catharine A. MacKinnon. Their completely new legal approach–in which pornography is defined as sex discrimination and therefore a violation of civil rights–would allow anyone injured by pornography to fight back by filing a civil lawsuit against pornographers. First passed in December 1983 in Minneapolis, where it was supported by a grassroots coalition of women, people of color, neighborhood groups, and the city's welfare poor and working poor, this law has transformed the way people of conscience understand the devastating impact of pornography on women's right to equality. This new law also offers hope: an effective legal tool for making sex equality real. In this comprehensive and easy-to-read guidebook, now available on line, the coauthors of the anti-pornography civil-rights ordinance explain: How pornography hurts women and how and why the civil-rights ordinance would make a difference. Why the pornography is so important to women's equality. The truth about the antipornography civil-rights ordinance–what it is, what it does, what it means, how it works. Answers to the lies about it–lies that the media have spread to protect the pornography industry. What you can do to stop the pornographers and further women's equality. "The Ordinance does not take 'rights' away from anyone, . . . it takes the power to hurt women away from pornographers." –from Pornography and Civil Rights
Section: 142 pages ; 22 cm
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; discipline; droit; droits des femmes*; féminisme anti-porn; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; science politique et droit; sex1911; sexualité; sofia; thématiques; violences; états-unis

Homeward bound: American families in the Cold War era - May, Elaine Tyler (Basic Books, 1988)
In the 1950s, the term "containment" referred to the foreign policy-driven containment of Communism and atomic proliferation. Yet in Homeward Bound May demonstrates that there was also a domestic version of containment where the "sphere of influence" was the home. Within its walls, potentially dangerous social forces might be tamed, securing the fulfilling life to which postwar women and men aspired. Homeward Bound tells the story of domestic containment - how it emerged, how it affected the lives of those who tried to conform to it, and how it unraveled in the wake of the Vietnam era's assault on Cold War culture, when unwed mothers, feminists, and "secular humanists" became the new "enemy." This revised and updated edition includes the latest information on race, the culture wars, and current cultural and political controversies of the post-Cold War era.
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; amériques; approches et analyses; cold war; cours; discipline; division of household labor; division sexuelle du travail; famille; guerre froide; his4443; histoire; histoire des femmes*; histoire du féminisme; histoire et politique; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; thématiques; travail; travail domestique; états-unis

The sexual contract - Pateman, Carole (Standford University Press, 1988)
In this remarkably original work of political philosophy, one of today's foremost feminist theorist challenges the way contemporary society functions by questioning the standard interpretation of an idea that is deeply embedded in American and British political thought: that our rights and freedoms derive from the social contract explicated by Locke, Hobbes, and Rousseau and interpreted in the United States by the Founding Fathers.
Keywords: 1900-1999; 1980-1989; amériques; citoyenneté; contrat social; cours; discipline; droits des femmes*; fem1000; incontournable; philosophie politique; premier cycle; périodes historiques; régions géographiques; sciences humaines; thématiques; théories féministes; états-unis

Homosexualités et tolérance sociale - Richard, Louis; Seguin, Marie-Thérèse; Groupe de recherche interuniversitaire et interdisciplinaire sur la gestion sociale (Éditions d'Acadie, 1988)
GRIIGES, Groupe de recherche interuniversitaire et interdisciplinaire sur la gestion sociale. Actes d'un colloque tenu du 9 au 11 oct. 1987 à l'Université de Moncton.
Section: 194 pages ; 23 cm
Keywords: 1900-1999; 1980-1989; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; homophobie; hétérosexisme; identités LGBTQIA2+; inégalités; justice sociale; nouveau-brunswick; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques

Écrire dans la maison du père : l'émergence du féminin dans la tradition littéraire du Québec. - Smart, Patricia (Québec/Amérique, 1988)
Dans une analyse qui assoit ses bases sur un texte du XIXe siècle (Angélinede Montbrun de Laure Conan), Patricia Smart démontre que, parallèlement à son histoire à lui, il y a une autre histoire, modulée par une autre voix, qui donne à lire une autre perspective sur le pays et sur le réel. Dans cet essai capital, elle nous propose une lecture absolument nouvelle des textes majeurs de la littérature québécoise. Écrire dans la maison dupère fait la preuve qu'en repérant les marques de la différence sexuelle dans le texte québécois, on peut ouvrir de larges brèches dans la thématique nationale et laisser entrevoir une ouverture possible sur un avenir habitable...
Keywords: amériques; arts; cours; cycles supérieurs; discipline; fem1000; fem7000; lit3220; lit3495; premier cycle; québec; régions géographiques; thématiques; théories féministes; écriture des femmes*; études littéraires